Renewable Energy Impact on Distance Relay Power Swing Blocking and Fault Discrimination: A Review - Okeke C.; Lutfi O.M.; Hashim H.; Kadir M.Z.A.A.; Wahab N.I.A.; Emmanuel O.; Nwagbara S.; Chimeleze C. (Universiti Putra Malaysia Press, 2024)
The annual increase of the global load demand has led to higher penetration of inverter-based renewable energy resources like wind farms and solar PV into the modern grid system. Distance relay may mal-operate by incorrectly estimating line impedance as fault during swing scenarios considering the infeed contributions impact from renewable sources. The negative impact of these integrated power electronics-based devices on the power swing blocking (PSB) and out-of-steps tripping (OST) functions of the distance relay characteristics has not been extensively discussed in previous studies. This study divulges a comprehensive review of the various PSB and OST schemes studies conducted to prevent relay mal-operation during power swing (PS) and symmetrical faults. Also, the large-scale renewable resources penetrations impact the PS characteristic and trip decision operation of the distance relay divulged. The mining of distance relay event records for hidden useful knowledge deployment for intelligent PSB and OST functions is the future research direction. Using the distance relay divulged knowledge will assist in reducing the failure rate level of PSB and OST function distance relaying schemes, hence improving the degree of reliability/dependability of the power system under different operating conditions. Universiti Putra Malaysia Press.